The Contribution of Islamic Education to Character Formation in the Age of Digitalization - Hapid Hapid; Bilal Zakawali Al-Fathoni (UIN Sunan Gunung Djati Bandung, 2025)
The Qur'an is a life guide for Muslims, although it does not explain in detail about education. However, there are several terms related to education in this scripture. This article tries to explain the nature and purpose of education in Islam by discussing these terms according to linguists and educational thinkers. In conclusion, the terms tarbiyah, ta'lim, ta'dib, tazkiyah, and tahdhib indicate the character and purpose of education.In the view of the Qur'an, the purpose of education is divided into three points: first, to form a complete human being; second, developing the human dimension in religion, culture, and science; third, making humans responsible as servants of God and heirs of the Prophet. These goals aim to create a Muslim who follows the principle of rahmatan li al-'alamin (mercy for all nature). Thus, Islamic education in the Qur'an is not only about the transfer of knowledge, but also values. It also has to do with building good relationships with God, fellow humans, and the universe